Gamification in medical education: A new approach - Vikas V. Pawar; Dhairyasheel Pawar (Oral Oncology Reports)
Gamification in medical education may improve learning, motivation, and engagement. Using decision-making cards improves clinical thinking and diagnosis. Resistance and comprehensive assessment are challenges. However, game-based learning can make medical education more engaging and effective for instructors, students, and patients